2020
DOI: 10.1371/journal.pone.0228964
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of Jiaji Duck by whole genome re-sequencing

Abstract: Jiaji Duck (JJ) is a Muscovy duck species that possesses many superior characteristics, and it has become an important genetic resource in China. However, to date, its genetic characteristics and genetic relationship with other duck breeds have not been explored yet, which greatly limits the utilization of JJ. In the present study, we investigated the genome sequences of 15 individual ducks representing five different duck populations, including JJ, French Muscovy duck (FF), mallard (YD), hong duck (HD) and Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Geographical isolation rarely allows genomic communication, and the traditional free-range breeding pattern results in low selection intensity. The diversity and origin of some Chinese domestic duck breeds have been studied using molecular markers, including mitochondrial DNA (mtDNA) ( Zhang et al 2007 ; He et al 2008 ; Li et al 2010b ), microsatellite markers ( Li et al 2006 , 2010a ; Liu et al 2008 ), and single-nucleotide polymorphisms (SNPs) ( Gu et al 2020 ; Wang et al 2020 ). However, most studies on Guangxi ducks focused on infectious diseases ( Xie et al 2012a , b ; Peng et al 2013 ), sequence data ( Zhang et al 2014 ; Xie et al 2016a , b ; Zhang et al 2016 ) or only contained a few Guangxi duck breeds in their breed categories ( Liu et al 2008 ; Li et al 2010b ; Zhou et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Geographical isolation rarely allows genomic communication, and the traditional free-range breeding pattern results in low selection intensity. The diversity and origin of some Chinese domestic duck breeds have been studied using molecular markers, including mitochondrial DNA (mtDNA) ( Zhang et al 2007 ; He et al 2008 ; Li et al 2010b ), microsatellite markers ( Li et al 2006 , 2010a ; Liu et al 2008 ), and single-nucleotide polymorphisms (SNPs) ( Gu et al 2020 ; Wang et al 2020 ). However, most studies on Guangxi ducks focused on infectious diseases ( Xie et al 2012a , b ; Peng et al 2013 ), sequence data ( Zhang et al 2014 ; Xie et al 2016a , b ; Zhang et al 2016 ) or only contained a few Guangxi duck breeds in their breed categories ( Liu et al 2008 ; Li et al 2010b ; Zhou et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that two interferon genes ( IFNAR1 and IFNAR2 ) were simultaneously involved in these four pathways and that the tumor necrosis factor (TNF) gene and a TLR5 gene were independently involved in the Cytokine signaling pathway and the Toll-like receptor pathway, respectively (Additional file 15 : Table S12). Gu et al [ 26 ] also found that IFNAR1 and TLR5 exhibited Muscovy-specific SNPs. Signatures of positive selection and species-specific SNPs both indicated that these two Muscovy duck genes underwent adaptive evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Sample Size = number of genotypes sequenced. Species Sample size Premature stops Synonymous Non-synonymous Citation Ananas comosus 89 7,084 689,019 589,484 (Chen et al 2019 ) Arabidopsis thaliana 1,135 27,813 803,665 1,135,115 (1001 Genomes Consortium 2016 ) Bos indicus 20 1,132 255,296 155,251 (Iqbal et al 2019 ) Bos taurus 15 3,837 1,155,244 524,103 (Zhang et al 2019 ) Branchiostoma belcheri 20 11,487 2,818,189 1,467,863 (Bi et al 2020 ) Brassica napus 991 1,413 120,926 79,018 (Wu et al 2019 ) Caenorhabditis elegans 330 5,084 271,950 261,538 (Cook et al 2017 ) Cairina moschata 15 285 36,517 19,817 (Gu et al 2020 ) Canis lupus 722 11,273 540,063 332,559 (Plassais et al 2019 ) Capsella grandiflora 15 5,209 644,326 478,238 (Koenig et al 2019 ) Capsella orientalis 16 269 11,250 13,281 (Koenig et al 2019...…”
Section: The Historical Contextmentioning
confidence: 99%